ON THE IMPORTANCE OF TOURISM IN FORMING A HEALTHY LIFESTYLE IN PRIMARY SCHOOL CHILDREN - Irmatov Shavkat Anvarovich (Galaxy International Interdisciplinary Research Journal, 2024)
Education of a developed generation, and on this basis scientific substantiation of cultural and moral education of a healthy lifestyle in the development of social relations, analysis of the study of a lifestyle due to independence is an urgent task. Modernization of the country due to independence and creation of decent living conditions for the population, development of a variety of works on the formation of a healthy lifestyle.